An Eye for an Eye Makes Maxillofacial Prosthodontics Beautiful: A Case Report - Rasmita Samantaray1 , Krishna Nanda1 , Sitansu Sekhar Das2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Loss of eye causes physical and emotional disturbace in patient. Rehabilitating the missing eye with ocularprosthesis can alleviate their suffering and brings back confidence in them.Maxilla facial prosthesis includesartificial prosthesis that replaces missing part of facial region which are removed/lost due to trauma,congenitaldefects or any kind of malignancies. Customized occular prosthesis is one of the method of rehabilitatinga missing eye. The re are many method and materials used for fabrication of these prosthesis which hasalready been discussed in many literature,out of which acrylic resins prosthesis provides better esthetics.The y are economical and characterization is possible. This case report describes the use of stock iris andcustom made sclera made up of heat cure tooth colored acrylic.Acrylic resin provides various advantagesover stock prosthesis by mimicking the natural eye.